Present Value of an Annuity–A Formula Approach. - McCray, John H. (The Accounting Review, 1972)
The article informs that when a student is first introduced to the concepts of compound interest, the functional relationships between the different variables are often confusing. This author has been successful in introducing the concepts of the present value of an ordinary annuity by using: a formula approach, problems that relate directly to the individual, and a present value of an ordinary annuity table with at least 360 periods and interest rates expressed to facilitate compounding monthly. Several examples follow. Two points about the formula should be stressed. First, the formula contains four variables. If three are known, the fourth can easily be found algebraically. Second, since there are four variables (PVA, i,n, P), the formula can be used to solve four different types of problems.